2018
DOI: 10.15244/pjoes/69029
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Bacterial Diversity in Two Full-Scale Enhanced Biological Phosphate Removal Reactors Using 16S Amplicon Pyrosequencing

Abstract: Despite their stability and the widespread use of enhanced biological phosphorus removal (EBPR), little is known about their microbial composition and activity. In our study we investigated highthroughput pyrosequencing of bacterial communities from two full-scale EBPR reactors of South Africa. Findings indicated that both EBPRs harboured high bacterial similarity, ranging from 83 to 100% with a diverse community dominated by Proteobacteria (57.04 to 79.48% for failed EBPR and 61.7 to 85.39% for successful EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Namely, the surface layer contained more Actinobacteria and Bacteroidetes. Actinobacteria [35] and Bacteroidetes [39] mainly existed in the place where the organism is concentrated. The influent of the CRI was from the upper part uniformly, so the organism concentration on the surface was the highest, which caused the abundances of Actinobacteria and Bacteroidetes to be higher.…”
Section: Bacterial Community Composition At the Phylum Levelmentioning
confidence: 99%
“…Namely, the surface layer contained more Actinobacteria and Bacteroidetes. Actinobacteria [35] and Bacteroidetes [39] mainly existed in the place where the organism is concentrated. The influent of the CRI was from the upper part uniformly, so the organism concentration on the surface was the highest, which caused the abundances of Actinobacteria and Bacteroidetes to be higher.…”
Section: Bacterial Community Composition At the Phylum Levelmentioning
confidence: 99%
“…Recent studies on biological technologies targeting the removal of phosphates from aqueous solutions reported on the use of engineered environmental bacteria [4] and specifically grown bacterial consortia in biofilm bioreactors [5], as well as on the introduction of shifts in structure and functions of microbial communities [6]. Studies also reported on the introduction of supplemental materials [7,8] or specific bacterial species [9] to activated sludge aerobic reactors that enhanced phosphates removal.…”
Section: Introductionmentioning
confidence: 99%